Modeling of the melting characteristics of commercial paraffin wax in an inverted equilateral triangular enclosure: Effect of convective heat transfer boundary conditions. (16th February 2017) - Tabassum, Tonny; Hasan, Mainul; Begum, Latifa
ABSTRACT: A horizontal double-pipe heat exchanger with an inverted outer equilateral triangular tube is modeled to numerically investigate the low-temperature thermal energy storage capability of an impure phase change material (PCM). The energy source fluid (hot water) flows through the inner tube and transfers heat to the PCM (heat sink) residing in the annular gap. The results show that the inlet temperature of the heat transfer fluid (HTF) has a significant effect on the melting process compared with the mass flow rate (MFR). The configuration, as well the concentricity/eccentricity of the inner tube has a great influence on the energy storage.